Fitness to Stand Trial and Disability Discrimination: An International Critique of Australia. Issue 5 (3rd September 2017) - Freckelton, Ian; Keyzer, Patrick
Abstract : In Noble v Australia (2016) the United Nations Committee on the Rights of Persons with Disabilities determined that Australia was in violation of a series of its obligations under the United Nations Convention on the Rights of Persons with Disabilities. The decision was a response to a communication brought by an Indigenous man, Marlon Noble, who had been found unfit to stand trial, had not had the opportunity to plead not guilty, and had been detained in a prison for over a decade. This article reviews the reasoning in the decision, the subsequent response by the Australian government and an inquiry into Western Australia's fitness to stand trial legislation. It argues that reform is urgently required in jurisdictions that fail to accord procedural fairness and suitable assistance to persons whose disabilities may preclude their meaningful participation in the criminal justice system.